A Study of Multiple Scattering in BGO and LYSO Single Crystal Scintillators - Seingsanor, Kittipong; Limkitjaroenporn, Pruittipol; Kaewkhao, Jakrapong (Journal of Mathematical and Fundamental Sciences, 2016)
The angular distribution of multiple Compton scatterings from BGO and LYSO single crystal scintillators was studied at various scattering angles. Gamma photons with 662 keV energy, acquired from a 137Cs source, were used. The scattered photons were detected by a 51mm Ã— 51mm NaI(Tl) scintillation detector. The overall energy correlated to the total number of scattered incidents was analytically reconstructed. The research found that the multiply scattered incidents had the same energy as received from the singly scattered distribution, as the attribution of multiply scattered incidents near the 90° scattering angle revealed. The research results were in agreement with the theoretical calculations.